MANAGEMENT OF INSOMNIA - Liya Rosdiana Sholehah (Universitas Udayana, 2013)
Sleep is an essential component of health and well-being. The effects of insomnia, Whether as a primary or secondary symptoms, is a major health concern and should be closely studied and Examined across all age groups. There is growing evidence that the effects of insomnia on Adolescent's functioning is comparable to that of other major psychiatric disorders (eg, mood disorders, anxiety disorders, etc..). Insomnia is associated with significant negative Consequences, impairing functioning across a number of emotional, social, cognitive, and physical domains (Carskadon, 1999; Johnson, Roth, Schultz, & Breslau, 2006; Roberts, Roberts, & Duong, 2008b; Wolfson & Carskadon, 1998). Based on the academic literature to date, it is hypothesized that insomnia will be Significantly more prevalent among Adolescents of the female sex and among those reporting psychological and / or physical health concerns. The analyzes conducted included basic descriptive statistics (frequencies / percentages), bivariate analyzes (Chi-square tests), and a multiple logistic regression. The prevalence rate of insomnia in adolescents was 9.5%, with no significant association found between sex and insomnia. The multivariate analysis Showed Significantly insomnia to be associated with the presence of a chronic condition, selected mood disorders (12 months), in adolescents who are experiencing